2018
DOI: 10.1002/zaac.201800145
|View full text |Cite
|
Sign up to set email alerts
|

Halide‐Ion Diadducts of Perhalogenated Cyclopenta‐ and Cyclohexasilanes

Abstract: The halosilicates(II) [nBu 4 N] 2 [Si 6 Br 12 ·2Br] and [nBu 4 P] 2 [Si 6 I 12 ·2I] were prepared by mere addition of the appropriate halide salt to the corresponding disilane Si 2 X 6 (X = Br, I). In the first case, the Br 3 Si-substituted derivative [nBu 4 N] 2 [Si 7 Br 14 ·2Br] formed as a second product. We have been able to obtain single crystals of [Ph 4 P] 2 [Si 7 Br 14 ·2Br] by switching the Brsalt from [nBu 4 N]Br to [Ph 4 P]Br. All three compounds, [nBu 4 N] 2 [Si 6 Br 12 ·2Br] (monoclinic, P2 1 /c),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…Of particular interest among the scientific community is perhalogenated cyclohexasilanes, due to its ability to act as a multiple tetrel bond donor using the twelve available σ-holes. In fact, crystallographic studies [ 35 , 36 , 37 ] have shown that perhalogenated cyclohexasilanes can strongly bind electron-rich moieties, such as halide anions or organocyanides (such as acetonitrile). Several theoretical studies [ 38 , 39 , 40 , 41 ] have explored this possibility by theoretically analyzing a series of anion/lone pair-Si inverted sandwiched complexes and confirming their ability to behave as efficient ditopic anion receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest among the scientific community is perhalogenated cyclohexasilanes, due to its ability to act as a multiple tetrel bond donor using the twelve available σ-holes. In fact, crystallographic studies [ 35 , 36 , 37 ] have shown that perhalogenated cyclohexasilanes can strongly bind electron-rich moieties, such as halide anions or organocyanides (such as acetonitrile). Several theoretical studies [ 38 , 39 , 40 , 41 ] have explored this possibility by theoretically analyzing a series of anion/lone pair-Si inverted sandwiched complexes and confirming their ability to behave as efficient ditopic anion receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Although the fraction with the second longer retention time could be identified as 7 ( n = 3), its further characterization was unsuccessful due to its very low amount and low solubility. The condensation reaction also proceeded in toluene and benzotrifluoride, while the reaction in CD 2 Cl 2 afforded a complex mixture including i -Bu 2 SiCl 2 , indicating that the BPS cage decomposed in this condition. , Notably, DMAP is a suitable Lewis base in the condensation of the BPS: when other Lewis bases such as P t -Bu 3 , PPh 3 , and NEt 3 were used, the reactions in C 6 D 6 did not complete even at 80 °C for 24 h, although the formation of 6 (and 7 ) were observed in 1 H NMR spectra. The observed slower reactions probably emerged from high solubility of the corresponding base–TMSI complexes, which would cause the corresponding reverse reactions.…”
mentioning
confidence: 97%
“…Upon going from [2] to [1] and [0] , dichlorosilylenes (SiCl 2 ) are extruded from the cluster cores and dimethylgermylenes (GeMe 2 ) are incorporated. Formal cyclocondensation of 6 SiCl 2 moieties would give perchlorinated cyclohexasilane, which was indeed detected by 29 Si NMR spectroscopy in the form of [ cyclo ‐Si 6 Cl 12 ⋅ 2Cl] 2− [22–26] . The GeMe 2 fragments, in turn, must originate from cannibalized heteroadamantanes [2] and [1] .…”
Section: Resultsmentioning
confidence: 99%
“…Formal cyclocondensation of 6 SiCl 2 moieties would give perchlorinated cyclohexasilane, which was indeed detected by 29 Si NMR spectroscopy in the form of [ cyclo ‐Si 6 Cl 12 ⋅ 2Cl] 2− . [ 22 , 23 , 24 , 25 , 26 ] The GeMe 2 fragments, in turn, must originate from cannibalized heteroadamantanes [2] and [1] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation